Electrochemical Characterization of an Oleyl-coated Magnetite Nanoparticle-Modified Electrode - Murugappan, Krishnan; Silvester, Debbie; Chaudhary, Deeptangshu; Arrigan, Damien (John Wiley & Sons, Inc, 2014)
The electrochemical behavior of oleyl-coated Fe3O4 nanoparticles synthesized by chemical co-precipitation is investigated. An approach based on the formation of a film of nanoparticles on an electrode surface is employed together with cyclic voltammetry. Characterization by scanning electron microscopy, confocal Raman spectroscopy, and X-ray photoelectron spectroscopy shows that Fe3O4 nanoparticles with a particle size of 20 nm coated with oleic acid are synthesized. These nanoparticles show superparamagnetic behavior and form a homogeneous film from their solution when dried in air. The nanoparticle film electrodes display redox behavior in acidic media but not in alkaline media, which suggests that protons take part in the electrochemical reaction. It is estimated that there are about 240 layers of nanoparticles deposited on the surface and that only around 1% of these nanoparticles are electrochemically active. This is attributed to either the long-chain surfactant or the large number of layers of nanoparticles inhibiting the electron- transfer process.